(3NhGWQ aj GdEOGQI GdeYGUQI (B/s - (3GdSdej, Ydis ((3GdbGgQI(B: s (3OGQ ZQjH(B, s, 2001)
(3GdGJLGgGJ GdeYGUQI aj GdEOGQI(B- (3EOGQI GdJSjjQ(B- (3eSDhdjGJ GdEOGQI GdeYGUQI hJMOjGJ GdhGbY GdLOjO(B- (3GdYhdeI hJCKjQGJgG Ydi GdEOGQI(B- (3NhGWQ aj GdEOGQI GdeUQjI GdeYGUQI (B- (3GdJbfjI GdLOjOI hJCKjQGJgG Ydi GdEOGQI(B- (3GdEOGQI aj GdCdajI GdKGdKI(B- (3GdEOGQI ef efXhQ GSdGejs
Keywords: (3GdEOGQIs; (3GdJfXjes; (3GdYhdeIs